If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 = 5 + 3m Solving 20 = 5 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. 20 + -3m = 5 + 3m + -3m Combine like terms: 3m + -3m = 0 20 + -3m = 5 + 0 20 + -3m = 5 Add '-20' to each side of the equation. 20 + -20 + -3m = 5 + -20 Combine like terms: 20 + -20 = 0 0 + -3m = 5 + -20 -3m = 5 + -20 Combine like terms: 5 + -20 = -15 -3m = -15 Divide each side by '-3'. m = 5 Simplifying m = 5
| -4x+9+6x=23 | | (3x)/5=6/1 | | 10-2b^2=-88 | | 3x+8+3x=68 | | -2(k+5)=-4 | | 4(x+10)-7x=-2(x-13) | | 8=6+2u | | 3x+2=x^2-25 | | X^2+9=14 | | 5x+4+x=-14 | | X^2-3=25 | | 7n^2-3=445 | | 13-s=8 | | 2/3(n-(5/6))=2.5 | | 5k^2-7=238 | | 6+4x+5x=51 | | 12/c=3 | | 6x+5+65=14x-10 | | 2+x-3x=2 | | 14(v+2)-2v=3(4v+1)-11 | | 2(f+4)=18 | | 2,7x0,5x4/5 | | 34=6x+3x+7 | | 9=2s+5 | | 3t^4=-t^2+2 | | 2(j-15)-1=3 | | pq+4opx+qy+z=0 | | 64=2x+7x+1 | | 6x+3-x=-22 | | 20x^2-32x+12=0 | | 114=6x+3x+6 | | 31.25=w/5 |